Pemetaan Kerawanan Tanah Longsor di Hulu DAS Tanggul - Indra Nurtjahjaningtyas; Gatrawan Muchammad Albirru; Entin Hidayah (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2023)
Landslides are one of the natural disasters that often occur in the Upper Tanggul Watershed. This study aims to produce a landslide susceptibility map based on the Geographic Information System (GIS). Seven landslides conditioning factors used, namely land cover, river density, slope, aspect, elevation, curvature and Normalized Difference Vegetation Index (NDVI). Landslide susceptibility areas were mapped using the frequency ratio and weights-of-evidence methods. The accuracy of the landslide susceptibility maps generated from both methods is validated using the Area Under Curve (AUC). The estimation results of the AUC plot show that the susceptibility map using the frequency ratio model has an accuracy of 92,6% and the weights-of-evidence method has an accuracy of 90,1%.